2018
DOI: 10.1021/acs.jctc.8b00200
|View full text |Cite
|
Sign up to set email alerts
|

Spin States and Other Ligand–Field States of Aqua Complexes Revisited with Multireference ab Initio Calculations Including Solvation Effects

Abstract: High-level multireference (CASPT2, NEVPT2) calculations are reported for transition metal aqua complexes with electronic configurations from (3d) to (3d). We focus on the experimentally evidenced excitation energies to their various ligand-field states, including different spin states. By employing models accounting for both explicit and implicit solvation, we find that solvation effect may contribute up to 0.5 eV to the excitation energies depending on the charge of ion and character of the electronic transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
82
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(95 citation statements)
references
References 96 publications
11
82
2
Order By: Relevance
“…The major outlier identified is [Mn(NH 3 ) 6 ] 2+ , which is strongly low-spin in the standard active space but becomes high-spin like hexa-aqua Mn(II) with the extended active space, exhibiting greater active space dependence than had been observed in Mn(II) porphyrins (Yang et al, 2016) (Supplementary Table 1). This discrepancy is likely caused by orbital rotation of some active orbitals into the inactive metal 3 s /4 s orbitals, as suggested in recent work (Radoń and Drabik, 2018) on aqua complexes. After removing this outlier, the mean absolute difference between the standard and extended active space results for all Δ E H−L and Δ E H−I combinations is 3.3 kcal/mol for the hexa-aqua and 5.9 kcal/mol for the hexa-ammine complexes.…”
Section: Resultsmentioning
confidence: 83%
“…The major outlier identified is [Mn(NH 3 ) 6 ] 2+ , which is strongly low-spin in the standard active space but becomes high-spin like hexa-aqua Mn(II) with the extended active space, exhibiting greater active space dependence than had been observed in Mn(II) porphyrins (Yang et al, 2016) (Supplementary Table 1). This discrepancy is likely caused by orbital rotation of some active orbitals into the inactive metal 3 s /4 s orbitals, as suggested in recent work (Radoń and Drabik, 2018) on aqua complexes. After removing this outlier, the mean absolute difference between the standard and extended active space results for all Δ E H−L and Δ E H−I combinations is 3.3 kcal/mol for the hexa-aqua and 5.9 kcal/mol for the hexa-ammine complexes.…”
Section: Resultsmentioning
confidence: 83%
“…[11][12][13][14] Extensive effort has therefore been devoted to evaluate different quantum chemical approaches for spin-state energetics and numerous studies on Fe(II), Fe(III) and Co(II) species have been reported. [15][16][17][18][19][20][21][22][23][24][25] Recent examples include the 2017 study by Pierloot et al into the performance of CASPT2 and NEVPT2 to describe the spin-state energetics of TM ions, TM ions surrounded by point-charges, and a range of first-row TM complexes, 16 and Radoń's 2019 assessment of CCSD(T), CASPT2, NEVPT2, MRCI and DFT for the calculation of experimental spin-state data for four octahedral Fe(II) and Fe(III) complexes. 20 Additionally, density matrix renormalization group (DMRG) methods have found increasing use in the study of spin-state energetics of first-row TM complexes, particularly for systems where the TM centres are situated within extensively conjugated ligands (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The model focuses on the role of orbital overlap in the coordination to the metal, but ignores the electron donating capacity of the chelating ligand, assuming that the main identifier is the imine character of the coordination center. Environment effects are also neglected [26,27]. Albeit simple, the model has a quite surprising predictive power for this class of compounds.…”
Section: Introductionmentioning
confidence: 99%